Fenomenologi Mahasiswa Membangun Bisnis Online - Huda, Dien Fahmi; , S.Sos., M.I.Kom., Mutiah (The Commercium, 2022)
Online businesses or businesses that use networks in their use are now in great demand by the Indonesian people because they provide many conveniences and advantages in them. Online business is also in great demand by students in order to apply the knowledge that has been obtained in college or want to convey their ideas in their business. This study aims to find out what their motives, experiences, and how they interpret building an online business when they are still students. This study uses a phenomenological method with a qualitative research type and the selection of sources is divided into three people. Researchers used data collection techniques with interviews and observations. The results of the study indicate that prior to the meaning process, there were separate motives and experiences for the informants who were behind the meaning. There are two motives owned by the informants, namely the motive because (because the motive) already has the skills, wants to take advantage of something, starting from a hobby. motive for (in order to motive) so that it is not difficult to find work, can be consistent in developing business, and create something new. The communication experience for the three speakers included getting something new, getting lots of connections, knowing how to build brand awareness and marketing products, and getting consumer satisfaction. After the motive and experience, meaning can be created. The meaning of building an online business is a challenge to enter the business world, to make oneself more productive, as a struggle to be independent, as self-development, to be committed and responsible for the business that has been built and as a way to achieve its goals. Keywords: Entrepreneurial Student, Phenomenology, Online Business